2007
DOI: 10.1111/j.1399-3038.2007.00516.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of eosinophilia to intravenous immunoglobulin treatment failure in Kawasaki disease

Abstract: To investigate the role of eosinophils in Kawasaki disease (KD) and the relationship to initial intravenous immunoglobulin (IVIG) treatment failure. A retrospective analysis of all children who were admitted and met the criteria of KD between 1999 and 2005. The patients were divided into IVIG-responsive and IVIG-resistant groups. A total of 185 patients were enrolled during the study period. A series of blood eosinophils and biochemistry studies were correlated to the effectiveness of IVIG. The neutrophils per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
132
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 121 publications
(137 citation statements)
references
References 25 publications
5
132
0
Order By: Relevance
“…20,21 Several factors have been reported to be associated with refractory cases, including younger age, 22 male gender, 23 earlier presentation, 3 initial treatment before day 4 of fever, lower platelets, 3,22 lower hemoglobin, 3,24 higher white blood cell 25 and bands counts, 3 elevated C-reactive protein 3,19,22,24,26,27 and erythrocyte sedimentation rate, 18 elevated lactate dehydrogenase, 19,24 abnormal liver function, 3,19,22,23,26,27 lower serum albumin 23,28,29 and certain biomarkers, 30-33 among others. 3 Thus, failure to reduce inflammation and fever after immunoglobulin therapy are markers for immunoglobulin resistance in Kawasaki disease.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Several factors have been reported to be associated with refractory cases, including younger age, 22 male gender, 23 earlier presentation, 3 initial treatment before day 4 of fever, lower platelets, 3,22 lower hemoglobin, 3,24 higher white blood cell 25 and bands counts, 3 elevated C-reactive protein 3,19,22,24,26,27 and erythrocyte sedimentation rate, 18 elevated lactate dehydrogenase, 19,24 abnormal liver function, 3,19,22,23,26,27 lower serum albumin 23,28,29 and certain biomarkers, 30-33 among others. 3 Thus, failure to reduce inflammation and fever after immunoglobulin therapy are markers for immunoglobulin resistance in Kawasaki disease.…”
Section: Discussionmentioning
confidence: 99%
“…25 IVIG treatment responsiveness was defined as defervescence 48 h after the completion of IVIG treatment and no fever (temperature, 4381C) recurrence for at least 7 days after the initial IVIG treatment, with marked improvement of inflammatory signs. 7,26,27 Patients with IVIG resistance received another dose of IVIG (1-2 g/kg) or other anti-inflammatory regiments.…”
Section: Materials and Methods Patientsmentioning
confidence: 99%
“…This increase of eosinophils after IVIG treatment is inversely correlated with IVIG treatment failure in KD. (29) Further studies have shown that eosinophil changes after IVIG treatment were positively correlated with changes in interleukin (IL)-5 levels. An increase in eosinophils and IL-5 levels after IVIG treatment is inversely correlated with CAL formation.…”
Section: Introductionmentioning
confidence: 99%